UJI BERBAGAI DOSIS PUPUK HERBAFARM GRANUL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI SAWAH (Oryza sativa L.) DENGAN METODE SRI - AHMAD EFRIZAL; CHAIRIL EZWARD; SEPRIDO SEPRIDO (Jurnal Ilmiah Pertanian, 2019)
This report aims to understand response various herbafarm granule doses of growth and the production of rice (Oryza Sativa L.) fields with the SRI (System Of Rice Intensification). Draft use is a random (group shelves) non factorials namely fertilizer herbafarm granule consisting of 6 standard treatment consisting of 3 test, H0 (Without treatment), H1 (2,43 g/plot), H2 (4,86 g/plot), H3 (7,29 g/plot), H4 (9,72 g/plot), H5 (12,15 g/plot). Each treatment repeat three times, 18 units in order to obtain a plot / experiment, Every a plot there were 9 plants and 7 of them sample plants. The quantity of a crop a whole 162 plant. Then the data obtained by in statistically analysis, further by test different real bnj truthful , 5 percent the first. Based on the research done so it can be concluded that treatment fertilizer herbafarm granule with the SRI give impact on the real parameters, for observation age flowering ( 77.33 hst ) and aged harvest ( 109 .33 hst ) treatment is the best H1 treatment, As for the number of productive saplings (39.90 stem) and heavy of dried grain (87.48 gram) treatment is the best H4 treatment.